Pengaruh Massage Endorphine terhadap Penurunan Nyeri Punggung pada Ibu Hamil Trimester III di Wilayah Kerja Puskesmas Kuta Baro Aceh Besar - Fauziah Fauziah; Ellyza Fazlylawati; Wahyu Reci Fansari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
From the results of a survey in the Kuta Baro Aceh Besar Health Center Work Area, there were 15 pregnant women and as many as 9 women who complained of severe back pain which was felt due to increasing gestational age, on average pregnant women were entering the third trimester or were approaching HPL (Day Estimated Birth). Meanwhile, 6 other pregnant women said they also felt pain but could still overcome it by lying down or reducing activity. The aim of the research is to determine the effect of endorphine massage on reducing back pain in pregnant women in the third trimester in the work area of the Kuta Baro Health Center, Aceh Besar. This research uses the Pre-Experiment method. The sample in this study used purposive sampling, namely the researcher determined 15 respondents to be used as samples. The results of the research are that there is an effect of endorphine massage on reducing back pain in pregnant women in the third trimester in the work area of the Kuta Baro Aceh Besar Health Center with a value of p = 0.000. Researchers hope that respondents can use it as a reference or guideline in dealing with back pain experienced in the third trimester.